The Role and Mechanism of Cinnamon for Athlete Metabolism and Recovery Process: A Systematic Literature Review - Muhamad Fahmi Hasan; I Ketut Adnyana; Samsul Bahri; Hamidie Ronald Daniel Ray (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2022)
Athletes have a high need to maintain their performance to stay fit while performing a high training intensity and frequent exercise. It makes athletes have a high need for supplements. However, athletes are prohibited from taking supplements included in the doping category. The lowest risk of doping is herbal-based supplements. This study used a systematic review method. The screening employed the PRISMA method as the preferred reporting item for systematic review and meta-analyses. The articles were obtained from Scopus and Dimensions databases using “cinnamon” as the keyword. Furthermore, the words "cinnamon" and "athlete" were added so that the data were obtained more specific. The exclusion criteria of this study involved original article documents, while the inclusion criteria included not more than 5-year publications. In the article selecting process, there were four articles that fulfilled the inclusion and exclusion criteria stating that cinnamon was effective for preventing inflammation that had an impact on accelerating recovery in athletes. Cinnamomum zylanicum is the most effective type of cinnamon for athlete recovery. It is because Cinnamomum zylanicum contains the most Cinnamaldehyde to help speed up recovery, which is most suitable for athletes. Thus, cinnamon is expected to be an alternative supplement for athletes to improve their performance.